"Ach, Gott, yes, I wish I was back in Russia": Heimat in the Dress of North Dakota's Black Sea Germans. (2nd January 2020) - Martin, Nancy; Ulasewicz, Connie
Abstract : Early nineteenth-century Germans—emigrating first to Russia and then in the late nineteenth century to America—expressed a cultural contradiction in their dress, affirming pride in their ancestral home but also a willingness to selectively adopt items from the surrounding environment. Evidence suggests that while in Russia, their communities had been segregated both by choice and by dictate within an ethnically diverse population. Six garments, located in North Dakota—the final stop in their double diaspora, were studied to define their apparel choices and whether they had remained unchanged or affected by surrounding cultures while in Russia. The items revealed a gendered mixture that both retained traditional German dress practices but also adopted convenient choices from the cultures around them. All the items affirmed the German-Russian experience of Heimat—an intense pride in their Germanic heritage coupled with a unique affection and homesickness for their adopted Russian fatherland.